Aortic valve myxoma—A systematic review of published cases. Issue 11 (12th July 2021) - Sachdeva, Sonali; Desai, Rupak; Shamim, Sofia; Gandhi, Zainab; Shrivastava, Ashish; Patel, Divyank; Uzair Lodhi, Muhammad; Raina, Jilmil; Itare, Vikram; Mahmood, Ahmed; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Background: Aortic valve myxoma is the rarest location of the most common primary tumour of cardiac origin. Because of the paucity of data, there is little known about their clinical presentation, diagnosis and complications. Methods: PUBMED, EMBASE, SCOPUS and WEB OF SCIENCE were systematically searched to identify all published cases of aortic valve myxoma through October 2020. Descriptive statistics were used to report the data. Results: Aortic valve myxomas were more prevalent in young (mean age 41 years) male (75%) patients. It most commonly involved the right coronary cusp (50%). Cerebrovascular events (25%), dyspnoea (18.8%), and distal embolisation (18.8%) were found to be the most frequent complications. Echocardiography remains the diagnostic modality of choice in all cases, histopathology is used for confirmation. Most cases were treated with surgical excision (94%); concomitant aortic valve repair and mechanical aortic valve replacement were performed in 25% and 37.5% cases respectively. Sudden cardiac death was noted in one patient. Conclusion: Aortic valve myxomas are more often than not discovered in the context of embolic phenomenon or dyspnoea. The most feared complication is stroke, although mortality remains low in surgically managed cases.